CULTURAL AND HISTORICAL ESSENCE OF IRONY IN MODERN PHILOSOPHY - Geiko, S. M. (Anthropological Measurements of Philosophical Research, 2012)
The author of article researches the cultural and historical essence of irony in the modernphilosophy. The role of irrational searches of philosophical discourse of modernism in the processof «irony» term explication is argumented. The possibility of «irony» therapeutical functionexecution in post modernistic style of philosophical research is proved.